Low Protein Brown Rice for Preventing Progression of CKD and DKD to End Stage Renal Failure - Shaw Watanabe (Diabetes Research, 2018)
Chronic kidney disease (CKD) is pervasive into aging society, affecting permanent implications on patients’ life. Approximately 10% of the global population has CKD, and millions die each year. The prevalence of CKD was high in Latin America, Europe, East Asia and the Middle East, where approximately 12% of the population has CKD.1 Diabetic kidney disease (DKD) or diabetic nephropathy (DN) is a part of CKD when the patients have diabetes.2 Both CKD and DKD may progressively fall from a normal estimated glomerular filtration rate (eGFR >90 ml/min/1.73 m2) to less than 15, at which point the patient becomes end-stage kidney disease (ESKD). The status of DKD could be estimated by measuring the amount of urinary protein and the serum creatinine, which can be used to calculate the eGFR. Progression rate of CKD/DKD is recently reported by Warren et al3 who classified 15,517 participants in the communitybased Atherosclerosis Risk in Communities (ARIC) study by diabetes status. They quantified eGFR trajectories at four visits over 26 years. Adjusted mean eGFR decline over the full study period among participants without diabetes was − 1.4 ml/min/1.73 m2/ year, with undiagnosed diabetes was − 1.8 ml/min/year, and with diagnosed diabetes was − 2.5 ml/min/year.